Pengaruh Profitabilitas, Solvabilitas dan Kebijakan Dividen Terhadap Harga Saham LQ 45 - Japar Abner Nangga; Dina Ramba; Jemi Pabisangan Tahirs (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine whether there is an effect of financial performance and dividend policy on stock prices in companies listed on the IDX. This study uses 5 companies as research samples with data collection from 2019-2022. Measuring tools used in this study are Return On Assets (ROA), Debt To Equity Ratio (DER), and Dividend Payout Ratioi (DPR). After conducting the research, the researchers concluded that profitability has a positive and significant effect on stock prices, solvency has a negative and insignificant effect on stock prices, and dividend policy has a positive and significant effect on stock prices.This study aims to determine whether there is an effect of financial performance and dividend policy on stock prices in companies listed on the IDX. This study uses 5 companies as research samples with data collection from 2019-2022. Measuring tools used in this study are Return On Assets (ROA), Debt To Equity Ratio (DER), and Dividend Payout Ratioi (DPR). After conducting the research, the researchers concluded that profitability has a positive and significant effect on stock prices, solvency has a negative and insignificant effect on stock prices, and dividend policy has a positive and significant effect on stock prices.